Transformation of Character Education: The Effectiveness of the Integrated Islamic School Curriculum in Shaping Students’ Islamic Personality - Nur Muhammad Ihsanudin; Eko Setiawan; Ika Ratih Sulistiani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the implementation of the Integrated Islamic School (SIT) curriculum in fostering students’ Islamic character at SMAIT Al Uswah Tuban. It employs a qualitative approach using a case study design. Data were collected through observations, interviews with the principal, teachers, and students, as well as analysis of curriculum documents and instructional guidelines. Data analysis was conducted through data reduction, data display, verification, and triangulation to ensure the validity of the findings. The results indicate that curriculum planning is grounded in the principle of tawhid and the characteristics of the SIT curriculum, involving the participation of multiple stakeholders. The curriculum is implemented through the integration of the national curriculum, SIT graduate competency standards, and the pesantren curriculum, and is strengthened by flagship programs such as Qur’anic memorization (tahfidz), language development, and leadership training. Evaluation is conducted through observation, self-assessment, and the active involvement of teachers and parents. The implementation of the SIT curriculum contributes to the development of students’ Islamic character, particularly in the values of shidiq, amanah, tabligh, fathanah, and istiqamah. These character traits are cultivated through formal learning processes, non-formal activities, teacher role modeling, and school culture. However, several challenges were identified, including difficulties in aligning learning outcomes across multiple curricula, limited teacher readiness, misperceptions in practice, and inconsistencies in assessment. These findings present an effective model of Islamic character education at SMAIT Al Uswah Tuban. They not only reinforce theoretical perspectives on Islamic education and character formation within a tripartite curriculum integration framework but also provide practical contributions to curriculum implementation models in pesantren-based schools for similar institutions. Further research employing quantitative or comparative approaches is recommended to enhance the validity and generalizability of the findings.